A fejlődés ára vagy az elmaradottság átka? Az öngyilkosság alakulása Magyarország községeiben (Szociológiai Szemle, 2024)
The research reported in this paper tests two competing explanations of the rise in rural suicide. The first theory regards this increase as the result of the spread of modern industrial civilization into the countryside, whereas the second stresses the negative effect that the physical isolation of small settlements exerts on community integration. I tried to choose between these arguments by taking a random sample of 600 Hungarian villages and performing regression analysis, with suicide as the dependent variable and various measures of modernization as the independent variables. The results indicate that modernization decreases the risk of self-destruction and this impact cannot be due to differences in the composition of the population. It thus seems that the rise in rural suicide is not, as the first explanation suggests, a consequence of great socio-economic changes but, in keeping with the second argument, it is the result of backwardness, of villages being unable to join the main stream of development.